Biomonitoring of firefighters occupational exposure to polycyclic aromatic hydrocarbons during the 2014 hot season - Oliveira, M. (2016)
Human biomonitoring is an important tool in environmental medicine that is used to assess the level of internal exposure to environmental pollutants. Firefighters are one of the most exposed and least studied occupations. During fire suppression, firefighters are heavily exposed to a wide range of chemicals. Polycyclic aromatic hydrocarbons (PAH) are ubiquitous environmental pollutants that are considered as the largest known group of carcinogens due to their cytotoxic and mutagenic properties. Smoke and ashes released during a fire are important sources of PAH. Firefighters can be also exposed to PAH through smoking, via polluted ambient air, water, soil, and through consumption of food. Metabolites of PAH (OH-PAHs), such as 1-hydroxynaphthalene (1OHNapt), 1-hydroxyacenaphthene(1OHAce), 1-hydroxypyrene (1OHPy) and 3-hydroxybenzo[a]pyrene (3OHB[a]P) have been used as biological markers for measurements of human internal exposure to PAH. The present work aims to quantify the urinary metabolites of PAH, namely 1OHNapt, 1OHAce, 1OHPy and 3OHB[a]P in study population of firefighters. Firemen exposed to fires that occurred during 2014 season were asked to fill a post-fire questionnaire and to collect urinary samples. A control study population group was selected to collect samples of urines during the pre-fires season (winter). Among all participating firemen only healthy no-smoking subjects were considered. OH-PAHs were analysed by high-performance liquid chromatography with fluorescence detection. Overall, 1OHNapt and 1OHAce were the most abundant OH-PAHs in firemen urine samples, accounting for approximately 90% of the total OH-PAHs. The urinary OH-PAHs in exposed firefighters were higher than those of control group. Data collected with the individual questionnaire were further used to analyse the concentrations of OH-PAH between (and within) control and exposed groups of firemen. Additionally, 1OHPy concentrations in the exposed firefighters will be compared with the available proposed guidelines.